EVALUASI PROGRAM TAHFIDZ AL-QUR’AN DALAM MENINGKATKAN MUTU PEMBELAJARAN DI MADRASAH DINIYAH AR-RAZAQ - Moh Rajul; Ahmad Fauzi; Mohamad Solihin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Qur’anic memorization (tahfidz) program has increasingly become an important indicator of quality in Islamic educational institutions. However, its implementation is often focused more on the achievement of memorization targets than on improving the overall quality of learning. This condition necessitates a comprehensive evaluation to ensure that the tahfidz program contributes not only to students’ memorization achievements but also to educational quality enhancement. This study aims to evaluate the Qur’anic tahfidz program at Madrasah Diniyah Ar-Razaq and examine its contribution to improving learning quality. The research employed a descriptive qualitative approach using the CIPP (Context, Input, Process, Product) evaluation model. Data were collected through participatory observation, in-depth interviews with the head of the madrasah, program coordinator, and tahfidz teachers, as well as document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, consisting of data condensation, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the tahfidz program is highly relevant to community needs and institutional goals, supported by adequate resources, and implemented through a structured and sustainable learning process. The program not only improves students’ memorization achievement and Qur’anic recitation quality but also fosters learning discipline, academic motivation, and a Qur’anic learning culture that contributes to overall educational quality. This study proposes an Integrative Tahfidz-Quality Evaluation Model that links memorization outcomes with the quality of the learning process through a continuous improvement framework. The findings imply that tahfidz program evaluation should be oriented toward the holistic and sustainable development of Islamic educational quality.